TPU/PLA nanocomposites with improved mechanical and shape memory properties fabricated via phase morphology control and incorporation of multi‐walled carbon nanotubes nanofillers. Issue 6 (5th March 2020) - Guo, Yi; Yan, Lei; Zeng, Zhu; Chen, Lin; Ma, Mingxue; Luo, Rui; Bian, Jun; Lin, Hailan; Chen, Daiqiang
Abstract: Shape memory polymer nanocomposites based on thermoplastic polyurethane (TPU)/polylactic acid (PLA) blends filled with pristine multi‐walled carbon nanotubes (MWCNTs) and modified MWCNTs─COOH were fabricated by direct melt blending technique and investigated for its morphology, mechanical, thermal, electrical, and shape memory properties. Morphological characterizations by using transmission electron microscope (TEM) and field emission scanning electron microscope (FESEM) revealed better dispersion of MWCNTs─COOH in the polymer blend, which is attributed to the improved interfacial interactions between the polymer blends and MWCNTs‐COOH. Loading of the MWCNTs‐COOH in the TPU/PLA blends resulted in the significant improvements in the mechanical properties such as tensile strength and elastic modulus and these effects are more pronounced on increasing the MWCNTs─COOH loading amount, when compared to the pristine MWCNTs filled system. Thermal analysis showed that the glass transition temperature of the blends increases slightly with increasing loading of both pristine and modified MWCNTs in the system. The resistance of nanocomposites decreased from 2 × 10 12  Ω to 3.2 × 10 10  Ω after adding 3% MWCNTs─COOH. The shape memory performance tests showed that the enhancement of shape recovery by 252% could be achieved at 3% MWCNTs loading, when compared to that of TPU/PLA blends.